Identidades em trânsito: um estudo dos sujeitos discentes estrangeiros na UFMA - COSTA, Clara Cardoso Ferreira (2020)
Born in the mid-1960s, the internationalization policies of Brazilian higher education institutions have been reinforced by the increased traffic of people in the world, a consequence of the globalization phenomenon. In this scenario, the research aimed to comprehend the cultural identitities construction, deconstruction and reconstruction processes of the foreign students of Maranhão’s Federal University (UFMA), influenced by their condition as subjects in transit. In order to do this, the research provides two moments. The first one consists in the composition of a theoretical framework, with concepts such as Culture, Place, Identity, Dislocation, Migration and Memory and supported by authors such as Teixeira Coelho, Franz Boas, Yi-Fu Tuan, Eric Dardel, Edward Relph, Stuart Hall, Tomaz Tadeu da Silva, Kathryn Woodward, Edward Said, Ernesto Laclau, André Braz Golgher, Homi K. Bhabha, Pierre Nora, Maurice Halbwachs, Joël Candau and Ecléa Bosi. The second and empirical one consisted of a data and documental collection, in order to identify UFMA’s student body and organizational structure. After this stage, the research’s contour was delimited to the participants of the Exchange Program for Undergraduate Students (PEC-G). Finally, an ethnographic multiple cases study was carried out, with the purpose of collecting the subjects’ oral narratives. As a result, favorable answers to the hypotheses were found, which address subjects like the cultural shock and resistance phenomena, the influence programs like PEC-G have over the motivations that bring these foreign students to UFMA and their processes of identity.